Reflection as a Component of an Intercultural Educational Project: Case Study in the Pushkin State Russian Language Institutev (Proceedings of the International Conference on Future of Education, 2021)
The abstract should provide a comprehensive summary of the work performed, includingthe motivation of the research, aim of the research, methods of the research, main results of theresearch, contribution to the theory and practice of the research. For nine years, the Pushkin StateRussian Language Institute has been successfully using the educational and teaching technology -intercultural educational project (IEP) - in teaching Russian as a foreign language. The goal of theproject is to ensure intercultural communication among all the participants: foreign students andMoscow schoolchildren. During this project, the audience gets acquainted with the differencesbetween languages and cultures. The specifics of this format of educational and design activities isdetermined by the relevant factors: the collaboration of foreign students studying Russian, and theother -, native speakers of the Russian language and culture. For the Moscow schoolchildren, theproject is a part of their training activities, for the students – an extracurricular educational event.Also, the project concept assumes that both students and children can also become more familiarwith (for example, Finland and Vietnam, etc.) each other's cultures. During the implementation ofthis technology, representatives of 34 countries took part in it, as well as more than 5,000 Moscowschoolchildren and teachers. The components of reflection are the ability to comprehend themechanisms that contribute to obtaining certain results; ability to analyze personal cognitiveopportunities. Reflection in the educational process implies a thoughtful or sensually experiencedprocess of awareness by the subject of his academic activities. The article aims to present thereflection component of IEP that the authors of the article draw special attention. Participation in thepreparation and implementation of activities that demonstrate the results of students' reflection,reflects the availability of intercultural communication at different levels of language proficiency,enables participants to feel confident in their abilities, motivate them, and increase the effectivenessof language learning. Authors hope that theoretical and practical aspects will contribute to themethods of teaching any foreign language.
Keywords: reflection; intercultural communication; educational technology; international educational project